SPOTLIGHT Pemenang Oscar “Film Terbaik” MEMBONGKAR KORUPSI SISTEMIK DALAM INSTITUSI GEREJA - John Mansford Prior (Institut Filsafat dan Teknologi Kreatif Ledalero, 2016)
This essay begins as a reflection on the Oscar award winning documentary Spotlight which relates how an investigative team of journalists at The Boston Globe in 2002 uncovered the extent of the sexual abuse of minors by clergy in the Archdiocese of Boston, and its systematic cover-up by Church and civic leaders. The investigation moved from a study of individual cases to the corrupt culture endemic in a hierarchical Church run by a caste of “celibate” males. The scandal is global, and remains with us today. The essential shift from the priority of avoiding scandal (and thus covering-up) to the placing of the victim at the centre, has yet to become consistent policy. Spotlight’s relevance to the Indonesian Church’s culture of silence is clear. Urgency demands acknowledgement of past and present failure, and immediate action to protect minors, punish offending priests, and put bishops who cover-up on trial. The clericalistic culture, so frequently condemned by Pope Francis, needs dismantling.